Descriptive Study of Certainty Level Towards Risk of Tuberculosis Disease in Productive Ages - Marlina, Lela; Darmansyah, Dhika (KnE Life Sciences, 2021)
Tuberculosis (TB) is caused by mycobacterium tuberculosis which can attack the organs of the body and is still a public health problem in the world despite many countries’ have effort to control the disease. 75% of pulmonary TB sufferers are found at the most economically productive age (15-49) years. The Objective to determine the level of certainty level in the risk of TB at productive age. The methods using a descriptive using cross sectional design. Conducted in June 2019, with research subject include of 133 respondents in the area of Pagarsih Public Health Center in Bandung City. The results showed the productive age affected by TB reached (96%) 128. At the age level showed that the most people affected by TB were at the age of 26 - 35 years (42%) as many as 56 people. In gender it mostly 53% female type. Characteristics of education are greater in high school education with a number (48%) 64 people. In greater occupations, such in unemployed/housewives the result showed (60%) or 80 people. Productive age should be concerned specifically because it is very susceptible to TB. Keywords: Certainty level, Tuberculosis, Productive Age.